The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/hrdq.21463
|View full text |Cite
|
Sign up to set email alerts
|

Does age matter? Examining career commitment as a moderator in the relationship between age‐related HR/D practices and subjective career success for younger versus older academic staff

Abstract: Building upon the job demands-resources framework and employing an interactionist perspective, the purpose of this scholarly work was to investigate the relationship between age-related HR/D practices (being a contextual antecedent) and career commitment (being a personal antecedent), and the interaction between these two, on the one hand, and subjective career experiences, on the other hand. Moreover, elaborating on life-span developmental theories and earlier empirical work on aging at work, this study also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 130 publications
2
8
0
Order By: Relevance
“…This outcome contrasts with the work of Hirschi et al (2018) who showed that career involvement was important for career success, operationalized in terms of salary and career satisfaction in several meta-analyses. However, in line with our findings, Van der Heijden et al (2021) also found no main effect of career commitment on subjective career success.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This outcome contrasts with the work of Hirschi et al (2018) who showed that career involvement was important for career success, operationalized in terms of salary and career satisfaction in several meta-analyses. However, in line with our findings, Van der Heijden et al (2021) also found no main effect of career commitment on subjective career success.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, similar to our scholarly work, Van der Heijden et al (2021) found that age differences played a significant role in the relationships between career commitment and career success outcomes. Our results also partly confirm Hypothesis 5 and indicate that age has an effect on the relationships between career commitment and developmental opportunities on the one hand and self-perceived employability on the other.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…MPlus 8.3 software was used to construct structural equation models for the latent variables in the Cross-lagged analysis, and the model was estimated using the robust weighted least square estimator (WLSMV) available [56], and holographic great likelihood estimation was used for the missing data [57]. Since age is a well-documented factor in career commitment [58,59], it was adjusted for in the model. The fit of all the models was evaluated using various indices as operationalized in Mplus in combination with the WLSMV estimator [60]: the WLSMV Chisquare statistic (χ 2 ), the Comparative Fit Index (CFI), the Tucker Lewis Index (TLI), the Root-Mean-Square Error of Approximation (RMSEA) and its 90% confidence interval.…”
Section: Discussionmentioning
confidence: 99%